2001
DOI: 10.1159/000053903
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum CA125 and CA15-3 Antigen Levels in Normal and Pathological Pregnancy

Abstract: Objective: To evaluate the value of maternal serum CA125 and CA15-3 concentrations for discriminating pathological from normal pregnancies. Methods: Serum samples from 120 women, in whom pregnancy outcome was pathological, i.e. spontaneous abortion, fetal death, intrauterine growth retardation, chromosomal and structural abnormalities, and (pre)eclampsia, were assessed for CA125 and CA15-3 and compared with levels found in 350 women with a normal pregnancy outcome matched for age and duration of pregnancy. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 13 publications
5
41
1
2
Order By: Relevance
“…27,28 Given the demonstrated immunomodulatory roles of sMUC16, 7,8 we next determined whether there were any differences in the binding pattern of this mucin to immune cells in preeclamptic patients compared with healthy pregnant women. First, we confirmed the results of previous studies 22,29,30 that the serum CA125 levels were not significantly different between healthy pregnant women and preeclampsia patients (Fig. 5a).…”
Section: Muc16 Binding To Immune Cells Of Patients With Preeclampsiasupporting
confidence: 91%
See 2 more Smart Citations
“…27,28 Given the demonstrated immunomodulatory roles of sMUC16, 7,8 we next determined whether there were any differences in the binding pattern of this mucin to immune cells in preeclamptic patients compared with healthy pregnant women. First, we confirmed the results of previous studies 22,29,30 that the serum CA125 levels were not significantly different between healthy pregnant women and preeclampsia patients (Fig. 5a).…”
Section: Muc16 Binding To Immune Cells Of Patients With Preeclampsiasupporting
confidence: 91%
“…22,25 We therefore monitored serum CA125 levels and immune cell bound sMUC16 in three women before and at 9 and 18 weeks of pregnancy. A gradual increase in serum CA125 was observed at 9 weeks of pregnancy.…”
Section: Nk Cell Bound Smuc16 Is Detected Even At Low Serum Ca125 Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of women from the same study, Richards et al then measured anti-MUC1 antibodies and found that virtually all women less than age 40 had antibodies and this percentage declined with age (4), somewhat similar to the pattern we observed. It is well established that women have MUC1 and anti-MUC1 antibodies during pregnancy and breast-feeding, presumably due to changes within the breast or uterus that alter MUC1 expression, glycosylation, or shedding (4,15,16). In addition, Hinoda et al observed antibodies specific for the peptide backbone of MUC1 in patients with ulcerative colitis and speculated that inflammation may change MUC1 glycosylation and enhance its immunogenicity (17).…”
Section: Discussionmentioning
confidence: 99%
“…[8, 9], in the majority of patients with prostatic cancer [10]as well as in sporadic cases of pancreatic cancer [11], in cases of chondroid syringoma [12]and in some hematological malignancies (<5% of the cases) [8, 13]. A mild-to-moderate increase of serum CA-15.3 has been noted among normal subjects, mainly in association with aging [14], pregnancy, with no difference in relation to normal or pathological pregnancy [15]and in various nonmalignant diseases and conditions [16], while it appears that renal failure does not significantly influence serum levels of this mucin [17]. Finally, elevated CA-15.3 levels were found in about 10% of patients with liver cirrhosis [18].…”
Section: Introductionmentioning
confidence: 99%